رائد سالم خضير باستخدام نظام هجين من خوارزميه جينيه وتحويل مويجي الصور احادي الموجهChain تحسين عمل نظام - سالمرائده (University of Thi-Qar Journal of Science, 2019)
The process of increasing compression ratio of images transmitted via the Internet is very important because it reduces the time required for sending and receiving as well as to reduce cost and the (Chain) system is one of the systems used to compression these images. The research aims is the improving of the system performance by amendment the image in order to obtain better presentation after the compression which use the wavelet transform . The image match rate is also increased more by using hybrid system of fuzzy logic and genetic algorithms(image rate is the ratio between the compressed image to the original image] this criterion is called PSNR(the ratio of the Peak Signal To Noise Ratio). The integration between the wavelet conversion and the suggested hybrid system was contributed effectively to the solve all problems of the (Chain) system by increasing the image match rates, and removing the distinct image massive influence .